Uterus inguinal hernia accompaniment didelphys uterus: A case report - Deng, Yang (Int J Surg Case Rep, 2020)
INTRODUCTION: Inguinal hernia encompassing the uterus, ovary and fallopian tube are uncommonly present in women of reproductive age, which is often diagnosed and treated during childhood. In this article we report a case of uterus inguinal hernia accompaniment didelphys uterus were confirmed during surgery. PRESENTATION OF CASE: A 15-year-old female presented with a history of a reducible mass located in the right inguinal region. Surgery was performed through an inguinal approach and the entire infantile uterus, both ovary and fallopian tube were found within the hernia sac. Laparoscopic exploration confirmed a normal uterus in the pelvic cavity, and the patient was discharged 3 days after the Lichtenstein operation. DISCUSSION: Although inguinal herniation is a common condition that occurs most often in elderly male and without any associated clinical symptoms. But uterine inguinal herniation should be considered as a reducible mass showed in the inguinal region. For open surgery, laparoscopy can be clearly diagnosed if it’s necessary to avoid blindly cutting and ligating important structures, which may affect fertility function after operation. CONCLUSION: Before the final choice of treatment is made, digestive surgeons should bear this rare hernia of uterine in mind for the differential diagnosis of an inguinal masses in women of child-bearing period. Congenital deformity genital organ, meanwhile, also should be considered.